Study of Architecture Aspect of Creative Economy in Sustainable Tourism at Simanindo - Melanie; Nurlisa Ginting (Talenta Publisher, 2022)
The architecture aspect in the creative economy is to provide a unique environment that involves art, emotion, activity, and culture. The architecture aspect is helping the development of sustainable tourism. Because of that, it is crucial to study the architecture aspect of sustainable tourism. Simanindo District is one of the districts in the center of Toba Lake and has many potentials to develop its tourism. The research has aims to identify the architecture in a tourism and local community opinions. The research methods used are qualitative and quantitative or usually called the mixed method. The data collections are collected from 100 questionnaires, interviews with four interviewees, and observation, and then the result will be analyzed and explained using analyze descriptive method. The final result from this research is an assessment from local communities against the culinary aspect in three aspects in sustainable tourism, economy aspect, socio-culture aspect, and environmental aspect. The conclusions are opinions and perceptions from the local community against architecture in sustainable tourism at Simanindo.